A Sociological Study of the Military Profession in Turkey: Profession, Duty, or Lifestyle? - Barış Ateş (İstanbul Üniversitesi Sosyoloji Dergisi)
This article aims to conduct a sociological analysis of the military profession in Turkey. Despite the prominent position of the army as an institution and the soldier as an individual in society and the state bureaucracy, its analysis as a social phenomenon has received little attention. This situation complicates the understanding of the military profession and creates conceptual confusion. Therefore, a theoretical discussion of the military profession and examination of its concepts are necessary. A descriptive survey with 695 participants was undertaken to bolster this theoretical debate and better understand citizens’ and soldiers’ perspectives on the military profession in Turkey. In addition, the study was supported by the unstructured interview method in order to increase the reliability of the survey results and enable a more profound analysis. As a result, mixedmethods research was used to resolve the data collecting constraints and sketch a broad picture of the military profession. Contrary to common perception, citizens and soldiers were shown to hold divergent views on the military profession. While soldiers refer to their job as a way of life, civilians refer to it as a profession and a duty. Another important finding of the study is that the understanding of professionalism among soldiers is mainly associated with seniority and experience. In addition, a continuity was observed to exist between the old and new generations of soldiers regarding their perception of the profession.